How to improve immune reconstitution in allogeneic hematopoietic stem cell transplantation? - Antoine Toubert (Frontiers Research Topics, 2015)
Allogeneic haematopoietic stem cell transplantation (allo-HSCT) is widely used in the treatment of haematological malignancies as a form of immunotherapy acting through a graft-versus-leukemia (GvL) reaction. This curative allogeneic response can be associated with severe drawbacks, such as frequent and severe graft-versus-host disease (GvHD) and a long-lasting immunodeficiency, especially now with the development of innovative strategies such as umbilical cord blood transplantation or transplants from haplo-identical family donors (Haplo-HSCT). In the long-term follow-up of these patients, severe post-transplant infections, relapse or secondary malignancies may be directly related to persistent immune defects.Reconstitution of the different lymphocyte populations (B, T, NK, NKT) and antigen presenting cells of myeloid origin (monocytes, macrophages and dendritic cells) should be considered not only quantitatively but especially qualitatively, in terms of functional subsets. Immune deficiency leading to an increased susceptibility to infections lasts for more than a year. Although infections that occur in the first month mostly result from a deficiency in both granulocytes and mononuclear cells (MNC), later post-engraftment infections are due to a deficiency in MNC subsets, primarily CD4 T-cells and B-cells. T-cell reconstitution has been extensively studied because of the central role of T-cells in mediating both GvHD, evidenced by the reduced incidence of this complication following T-Cell depletion, and a GvL effect as shown by DLI. In the recent years there has been renewed interest in the role of NK-cells, especially in the context of Haplo-HSCT, and in B-cell reconstitution.This Frontiers Research Topic will provide state of the art knowledge of the mechanisms of immune reconstitution in an allogeneic environment, in order to improve monitoring and therapeutic intervention in allo-HSCT patients.